Menopause: Mental Health, Health Issues, and Coping Strategies. A Qualitative Study - Mamnuah Mamnuah; Wawan Febri Ramdani; Farida Kartini; Dhesi Astuti; Dian Retnaningdiah; Wantonoro Wantonoro (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Menopause marked a transformative phase in many women’s lives, often accompanied by complex physical, emotional, and social challenges. This study aimed to explore how women in Yogyakarta experienced and managed menopause, shedding light on their unique coping strategies and support systems. A qualitative design employed purposive sampling to recruit women aged 45 to 55, ensuring diverse and relevant experiences. In-depth, face-to-face interviews were conducted and analyzed thematically to uncover underlying patterns and meanings. Four major themes emerged: physical and emotional changes, adaptation strategies, social support dynamics, and shifts in sexuality. Women reported symptoms such as sleep disruption, fatigue, and mood instability, and adapted by seeking information and modifying their lifestyles, although resources were often insufficient. Family and community support provided essential emotional relief, while changes in intimacy required communication and adjustment. These findings highlighted the need for holistic menopause management that integrates physical, emotional, and relational support.